Qualitative Field Research in Anthropology: An Overview of Basic Research Methodology - Bojan Žikić (University of Belgrade, 2016)
Methodology of qualitative anthropology study is presented, as it was used in investigating HIV/HCV vulnerability in Belgrade injecting drug users and sex workers, as well in documenting lives of people living with HIV. Fieldwork techniques, ethical considerations, and some wider contribution of research of this type to the health issues particularly have been reviewed.